Kościół i parafia Matki Boskiej Nieustającej Pomocy w Bydgoszczy na Szwederowie w latach 1920-1945 (Kronika Bydgoska, 2020)
This article features a brief history of the Church and Parish of Our Lady of Perpetual Help in Szwederowo, Bydgoszcz in 1920-1945. The parish was described from the time of establishing an independent pastoral district, taking into consideration statistics regarding baptisms, marriages, and deaths. It reported the most important events from the life of the parish, including visits of the clergy, retreats, and Holy Missions. The article also informed about construction of the church and parish buildings by the first parish priest, Fr. Jan Konopczyński. This study confirms the role of the Church in the Polish state formation after the return of the city to the Homeland.